PREPARATION, CHARACTERIZATION AND USED OF POLYSULFONE MEMBRANES FOR THE TREATMENT OF WATER SOLUTIONS CONTAINING HUMIC ACIDS - Ni Nyoman Rupiasih; Made Sumadiyasa; A.A. Ratnawati; Hery Suyanto (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2011)
PREPARATION, CHARACTERIZATION AND USED OF POLYSULFONE MEMBRANES FOR THE TREATMENT OF WATER SOLUTIONS CONTAINING HUMIC ACIDS. Polysulfone (PSf) membranes were cast by phase inversion method using PSf as matrix, N,N-Dimethylacetamide (DMAc) as solvent and distilled water as coagulant. The microporous membrane has studied using Scanning Electron Microscope (SEM) and filtration techniques. The filtration experiments were performed on a flat sheet membrane using pure water and humic acids (HA) solution as feeds. The results show, the Pure Water Flux (PWF) and Product Flux (PF) values decrease with increasing thickness of the membranes. They are consistent with the SEM images that thicker membranes have smaller pore size and less in numbers. The Rejection coefficient (R) values showthat the membranes are able to filter HA in the form of solution, with the performance dependent on the characteristics: thickness and microporous structure. They were increased with increase in the thickness of the membranes and with increase in the wavelength from 250-665 nm. It suggests that, the PSf membranes can be used to minimize the amount of Humic Acids from water process to improve the quality of treated to an acceptable quality level.